1997
DOI: 10.1088/0957-0233/8/12/013
|View full text |Cite
|
Sign up to set email alerts
|

Particle image velocimetry for predictions of acceleration fields and force within fluid flows

Abstract: We describe an experimental investigation of various methods of using the non-intrusive particle image velocimetry (PIV) technology to obtain the acceleration field of fluid flows and particularly the force being exchanged between a fluid flow and its boundaries. Methods based on the Lagrangian and the Eulerian specifications respectively have been developed, applied to experiments and compared. The experiments were performed by using a four-CCD-camera system designed to acquire between two and four frames in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 6 publications
0
30
0
Order By: Relevance
“…Christensen and Adrian (2002) found that for their advecting turbulence experiment, the material acceleration was about one order of magnitude smaller than the time change of the velocity at one point, which would also promote the use of a Lagrangian approach. On the other hand, Jakobsen et al (1997) found that for waves impinging on a vertical wall, their Lagrangian approach had limitations and showed bias effects, resulting in a worse performance than their Eulerian approach. These contradictory results show the need of a direct comparison of the two approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Christensen and Adrian (2002) found that for their advecting turbulence experiment, the material acceleration was about one order of magnitude smaller than the time change of the velocity at one point, which would also promote the use of a Lagrangian approach. On the other hand, Jakobsen et al (1997) found that for waves impinging on a vertical wall, their Lagrangian approach had limitations and showed bias effects, resulting in a worse performance than their Eulerian approach. These contradictory results show the need of a direct comparison of the two approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Unal et al (1998) used a momentum-based approach to determine the instantaneous force on a circular cylinder. Two methods based on the Lagrangian and the Eulerian specifications are compared by Jakobsen et al (1997) using a four-CCD-camera system to predict the acceleration field from velocity measurements in wave phenomena. In the Eulerian description of fluid motion all variables are taken to be functions of time and local position, rather than initial position as in the case of Lagrangian description.…”
Section: Introductionmentioning
confidence: 99%
“…Assuming that the temporal velocity gradient is approximately constant or linear in time within the time interval between the two snapshots, dt, and for all spatial locations (Jakobsen et al, 1997), the acceleration at time t (eq. 3), as well as the pressure gradient (eq.…”
Section: Eulerian Approach (Eu)mentioning
confidence: 99%
“…However, the acceleration can also be determined using a Lagrangian approach and the comparison of the two methods has also been the focus of several recent works. Using PIV on surface waves to predict flow accelerations and forces, Jakobsen et al (1997) compared Eulerian and Lagrangian approaches and the results indicated that the former approach matched closely the analytical calculations. The Lagrangian approach exhibited a small bias, which led to a systematic error in the estimation of flow acceleration and seemed to be limited due to poor tracking or deformation of fluid volume.…”
mentioning
confidence: 94%